Synthesis of Ce0.75Zr0.25O2 at 100 degrees C - Dhage, S. R.; Gaikwad, S. R.; Muthukumar, P.; Ravi, V. (Ceramics International, 2005)
A simple gel to crystal conversion route has been used for the preparation of Ce0.75Zr0.25O2 phase at 80-100degreesC under refluxing conditions. Freshly prepared metal hydroxides gel from cerium and zirconium salt solution is allowed to crystallize under refluxing and stirring conditions for 4-10 h. Formation of nano crystallites of Ce0.75Zr0.25O2 is confirmed by X-ray diffraction (XRD). Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 5 nm. (C) 2004 Elsevier Ltd and Techna S.r.l. All rights reserved.
Keywords: CeO2; chemical preparation; Electron microscopy; powders; X-ray methods